2023
DOI: 10.1029/2023ja031350
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Kinetic Alfvén Waves to Energetic Electron Precipitation From the Plasma Sheet During a Substorm

Abstract: Energetic (≳50 keV) electron precipitation from the magnetosphere to the ionosphere during substorms can be important for magnetosphere‐ionosphere coupling. Using conjugate observations between the THEMIS, ELFIN, and DMSP spacecraft during a substorm, we have analyzed the energetic electron precipitation, the magnetospheric injection, and the associated plasma waves to examine the role of waves in pitch‐angle scattering plasma sheet electrons into the loss cone. During the substorm expansion phase, ELFIN‐A obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 183 publications
(364 reference statements)
0
4
0
Order By: Relevance
“…Figures 1i and 1j show that the flow bursts corresponded to enhanced broadband electrostatic fluctuations (or TDSs) with frequencies ranging from tens of Hz to several kHz. Additionally, sporadic electromagnetic wave power enhancements, mostly below ∼20 Hz, indicate the presence of kinetic Alfvén waves (KAWs) (e.g., Chaston et al., 2012; Malaspina et al., 2018; Shen et al., 2023).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figures 1i and 1j show that the flow bursts corresponded to enhanced broadband electrostatic fluctuations (or TDSs) with frequencies ranging from tens of Hz to several kHz. Additionally, sporadic electromagnetic wave power enhancements, mostly below ∼20 Hz, indicate the presence of kinetic Alfvén waves (KAWs) (e.g., Chaston et al., 2012; Malaspina et al., 2018; Shen et al., 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, TDSs are likely linked to red‐line‐dominated auroras, especially when the plasma sheet state is prime for such low‐energy precipitation, like quiet times with low temperatures. In fact, to reliably identify TDS‐driven diffuse auroras, non‐substorm conditions are more suitable, as it is often challenging to disentangle aggregated effects from different, concurrent drivers during substorms that preclude direct linkage to flow bursts and TDSs (e.g., Sergeev et al., 2012; Shen et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the BLC fluxes are an optimized estimate based on known physics and available instrumentation. Still, the pitch angle diffusion theory by Kennel and Petschek (1966) assumes steadystate conditions, which can lead to uncertainties in geomagnetic active periods (Shen et al, 2023). Moreover, a recent idealized model study by Selesnick et al (2020) points out that the sensitivity of the 0°detector outside the nominal field of view may cause it to be susceptible to quasi-trapped or trapped electrons during periods of weak pitch angle diffusion, hence exaggerating the fluxes.…”
Section: Nominal Lower Limitmentioning
confidence: 99%
“…Also, field-line curvature scattering is likely not significant during dipolarization when the magnetic field line curvature radius increases (Lukin et al, 2021), especially for electrons at high pitch angles (Buchner & Zelenyi, 1989;Delcourt et al, 1995). The kinetic Alfvén wave has recently been found to potentially contribute to the precipitation of >50 keV electrons from the substorm plasma sheet, but this scattering is most effective when KAW power is strong enough (Shen et al, 2022(Shen et al, , 2023, which is not always observed. Furthermore, the perpendicular anisotropy will be continuously fed by freshly injected electrons during a substorm, thus its lifetime is expected to be consistent with substorm timescales.…”
Section: Event On 7 September 2022mentioning
confidence: 99%